2017
DOI: 10.1136/esmoopen-2017-000227
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported pain severity, pain interference and health status in HR+/HER2− advanced/metastatic breast cancer

Abstract: IntroductionPatient-reported pain severity and related impact in advanced/metastatic breast cancer (ABC/MBC) are not well documented. The objective of this study was to assess pain and general health status in hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) ABC/MBC.MethodsData were collected in the USA and Europe in a real-world, cross-sectional study. Patients were recruited at oncology practices and completed validated questionnaires; pain severity and interference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…In our cohort, BPI "worst pain" was moderate/severe for 42% of patients, and "pain interference" was moderate/severe for 80% of patients. Increased pain severity has been associated with a worse HRQoL or health status in patients with advanced breast cancer [14,40,45]. However, patient-reported pain/discomfort was not an independent predictor of HRQoL in our regression analysis despite a high proportion (~70%) of the EU5 patients in our analysis reporting some/ extreme problems in the EQ-5D-3L domain of pain/discomfort.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In our cohort, BPI "worst pain" was moderate/severe for 42% of patients, and "pain interference" was moderate/severe for 80% of patients. Increased pain severity has been associated with a worse HRQoL or health status in patients with advanced breast cancer [14,40,45]. However, patient-reported pain/discomfort was not an independent predictor of HRQoL in our regression analysis despite a high proportion (~70%) of the EU5 patients in our analysis reporting some/ extreme problems in the EQ-5D-3L domain of pain/discomfort.…”
Section: Discussioncontrasting
confidence: 56%
“…PRO data on patients with advanced breast cancer in the real-world setting are limited, especially in those with HR+/HER2− disease [12][13][14][15][16][17]. Evidence is also lacking from European settings.…”
Section: Introductionmentioning
confidence: 99%
“…The primary study endpoint was to describe the health-utility score for the whole cohort. Previous studies on real-world QoL within breast cancer patients found several patient-, disease-, and treatment factors to exert a significant influence on the experienced QoL, including age [ 19 , 20 ], comorbidities [ 20 ], type of therapy [ 19 24 ], number of lines of therapy [ 21 , 24 ], location of metastases, [ 21 , 22 , 25 ], and disease progression [ 23 , 26 28 ]. Therefor, our secondary endpoints included differences in QoL between subgroups of patients based on age (≥ 65 versus < 65 years), comorbidity according to the Charlson index (yes versus no and multiple subdivisions in comorbidity), tumor subtype (hormone receptor (HR) and human epidermal growth factor receptor-2 (HER2) status), current treatment type (endocrine, chemo- and/or targeted therapy), total number of prior palliative treatment lines, and number and metastatic site(s).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a study of patients with painful metastatic bone cancer, moderate-to-severe pain interfered with the patients’ ability to walk, stand, and perform other activities. [47]…”
Section: Theoretical Framework: the Theory Of Unpleasant Symptomsmentioning
confidence: 99%